PENGARUH KUALITAS PELAYANAN DAN FASILITAS RUANG TUNGGU TERHADAP KEPUASAN PENGGUNA JASA BANDAR UDARA AJI PANGERAN TUMENGGUNG PRANOTO SAMARINDA 2024 - Sri Wahyuning; mutiara hapsari, cinthia; Purnama Andri Murdapa; Jikri Nurhafidh Mulki (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
Transportation in the current era has become an inseparable need for human life, because transportation is one of the tools that connects from one region to another, and transportation is one of the things that determines the development of a country, the more sophisticated the transportation of a country, the more advanced the country is. The purpose of this study is to determine the effect of service quality and facilities on service users at APT Pranoto Samarinda Airport. The research method used is quantitative. The research population is all service users, the sample used is 100 respondents. The research data was obtained through a questionnaire analyzed using the t and f tests. The results of the study show that: Service quality affects the satisfaction of service users which has a t-count value (2.03) > t table value (1.66) and a significant level (0.04) < (0.05). Facilities do not affect the satisfaction of service users which has a t-count value (0.27) < t table (1.66) and a significant level (0.78) > (0.05). and simultaneously the variables of service quality and facilities do not affect the satisfaction of service users where the calculated f value (2.096) < f table (3.09) and the level of significance (0.129) > (0.05).